1992
DOI: 10.1021/jm00080a013
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl-substituted analogs of oxotremorine as muscarinic antagonists

Abstract: A series of phenyl-substituted analogues of the muscarinic agent oxotremorine (1) have been prepared. The new compounds (3b-11b and 9c) were assayed for antimuscarinic activity on the isolated guinea pig ileum and in intact mice. They were also evaluated for ability to inhibit the binding of the muscarinic antagonist (-)-[3H]-N-methylscopolamine to homogenates of the rat cerebral cortex. The phenyl-substituted derivatives were devoid of intrinsic muscarinic activity. Instead, they behaved as competitive muscar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…A similar reaction pattern was reported by Hacksell et al, who reported a base-catalyzed isomerization of propargylic amides through allenic intermediates. [16] But the 1 H NMR data reported by Uemura et al did not match the symmetry of intermediate A, which should show only one resonance for the allenic CH 2 group, but two different resonances were reported in footnote 7 of the publication. Furthermore, such an intermediate would contradict our mechanistic findings: [6] As we considered the participation of intermediate dihydrooxazoles (Scheme 2, path b) in our publication, further experimental clarification of the mechanism was required.…”
Section: Resultsmentioning
confidence: 94%
“…A similar reaction pattern was reported by Hacksell et al, who reported a base-catalyzed isomerization of propargylic amides through allenic intermediates. [16] But the 1 H NMR data reported by Uemura et al did not match the symmetry of intermediate A, which should show only one resonance for the allenic CH 2 group, but two different resonances were reported in footnote 7 of the publication. Furthermore, such an intermediate would contradict our mechanistic findings: [6] As we considered the participation of intermediate dihydrooxazoles (Scheme 2, path b) in our publication, further experimental clarification of the mechanism was required.…”
Section: Resultsmentioning
confidence: 94%
“…Traditional methods for accessing these heterocycles start from carboxylic acids, esters, nitriles, hydroxyamides, aldehydes and olefins . Another versatile and effective way is the transition metal‐catalyzed cyclization of N ‐propargylcarboxamides, with Brønsted acids, or under strong basic conditions . Among these N,O ‐heterocycles, alkynyl‐substituted oxazolines represent a highly interesting class of functionalized building blocks for synthetic chemistry, a fruitful follow‐up chemistry is enabled by the subsequent functionalization of the alkynyl groups .…”
Section: Introductionmentioning
confidence: 99%
“…[1c] Another versatile and effective way is the transition metal-catalyzed cyclization of Npropargylcarboxamides, [5] with Brønsted acids, [6] or under strong basic conditions. [7] Among these N,Oheterocycles, alkynyl-substituted oxazolines represent a highly interesting class of functionalized building blocks for synthetic chemistry, a fruitful follow-up chemistry is enabled by the subsequent functionalization of the alkynyl groups. [8] Traditionally, these compounds are synthesized by Sonogashira cross coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Propargylamines are important synthetic intermediates for the preparation of natural products [1], potential therapeutic agents [2], oxotremorine analogues [3] and multifunctional amino derivatives [45]. Compounds like resagiline or selegiline (structures 1 and 2 , Scheme 1) bearing a propargylamine moiety, are familiar as potent selective, irreversible monoamine oxidase (MAO) type B inhibitors [6] often used for the treatment of neuropsychiatric disorders such as Alzheimer’s and Parkinson diseases.…”
Section: Introductionmentioning
confidence: 99%